If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2x + -6 + -4x = 6 Reorder the terms: 10 + -6 + -2x + -4x = 6 Combine like terms: 10 + -6 = 4 4 + -2x + -4x = 6 Combine like terms: -2x + -4x = -6x 4 + -6x = 6 Solving 4 + -6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -6x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -6x = 6 + -4 -6x = 6 + -4 Combine like terms: 6 + -4 = 2 -6x = 2 Divide each side by '-6'. x = -0.3333333333 Simplifying x = -0.3333333333
| 35+0.10m=25+0.25m | | 3z+4=-2 | | 1+6(k+6)=85 | | (32-20)/4= | | .05x+.25(30-x)=3.3 | | 0.6(y+3)=y+0.2 | | 5m-3[7-1(1-2m)]=0 | | 2+x(x-3)=20 | | 2x^2+5x-12=-5 | | 1x-10=-6x-10 | | (5m-6)(3m+1)=0 | | -10n-(8+8n)=-6(n-4) | | -35=4n-7 | | 16-3*4=52 | | a-13=-3a-1 | | (5m-1)(3m+6)=0 | | 3/8+b*5/8=-1 | | 2/3+x+6=3/4 | | h=-4.9t^2+15t+10 | | Y-1=-8 | | 15m^3+13m^2-6m=0 | | 32+4c(c-1)=(4c+5) | | x^3-3x+7=0 | | 6+x/(-8)=4/7 | | 16x^2-5x+9=-29x | | 3z^2-4z=-7 | | 7=6x-10 | | -9(2b+3)+(19b-5)=0 | | 8x+2=5x+17 | | 1.3(8-x)+3.7x=-5.2 | | -2(x+3)+3x=11 | | 6z^2+43z+7*7z^2+4z-6= |